The Relationship Of Knowledge And Support From Husbands To Family Planning Acceptors In Iud Choice In The Working Area Of Tanjung Pinang Health Center, Jambi - Usi Lanita; Naomi Elda Gracia Simamora; Sri Astuti Siregar; Kasyani, Kasyani (International Journal of Health Engineering and Technology, 2024)
The government's program to overcome population problems is family planning, and one way is through IUD contraception. IUD is a method that has a very small failure rate of less than 1% and is said to be the most effective contraceptive method for spacing and preventing births. The research aims to determine the relationship between knowledge and husbands' support for family planning acceptors in choosing an IUD in the Tanjung Pinang Community Health Center Working Area, Jambi. This is quantitative research through analytical observation with the case control method, consisting of 48 cases and 48 controls using a simple random sampling technique. Data were collected using a questionnaire, and analysis was carried out using the Chi-Square statistical test. The results of this study a relationship between knowledge (p-value 0.001) and husband's support (0.011) and the choice of IUD among family planning acceptors in the Tanjung Pinang Health Center Working Area, Jambi. There is a relationship between knowledge and support from husbands in choosing an IUD among family planning acceptors, so it is hoped that health workers will provide regular outreach regarding the use and benefits of IUD contraceptives to the community.